Deadliest volcanoes - Williams, Nathan; Williams, Nathan (PBS Home Video, 2012)
Millions of people around the world live in the shadow of active volcanoes. From Japan's Mount Fuji to the 'Sleeping Giant' submerged beneath Naples to the Yellowstone 'Supervolcano' in the United States, Nova travels with scientists who are attempting to discover how likely these volcanoes are to erupt, when it might happen, and exactly how deadly they could prove to be.